Adjective + yi dian in Mandarin Chinese and its equivalent in Indonesian language: A contrastive analysis - Wilujeng, Nuning Catur Sri; æ°æœˆ, èŒƒ (Diksi, 2022)
In the last decade, Mandarin Chinese has been standing as the most studied language as a foreign language. The structure of Mandarin Chinese is not necessarily similar to the grammatical structure of Mandarin Chinese learners. In daily life, structure of different ideas produces different pragmatic functions in the grammar. This article aims to describe the difference between the discourse of "adjective + a little bit" and Indonesia. The data source comes from the Modern Chinese Corpus of Academia Sinica, Taiwan. The stages of data analysis are data sorting, data classifying into four groups, and data analysis. From the corpus, there are 697 sentences withä¸€é»ž/ yi dian/ adverbs in "adjective +ã€ä¸€é»žã€‘/ yi dian/" includingã€æ¯”è¼ƒ+å½¢å®¹è©ž+ä¸€é»žã€‘or comparison+adjective+ã€ä¸€é»žã€‘/ yi dian/] and 56 sentence-word adverbs in "[adjective+particleã€äº†ã€‘/le/+ã€ä¸€é»žã€‘/ yi dian/]" which contains"ã€å¤ª+adjective" +äº†+ä¸€é»žã€‘. The first group of "adjective +ã€ä¸€é»žã€‘" category has (83.95%) sentences; there are 66 adjective categories with only one word such as: ã€å¥½ã€‘/hao/ good,ã€å¤šã€‘/duo/many,ã€å°ã€‘/xiao/small,ã€å¤§ã€‘/da/big, etc. and 554 have two words such as: ã€å¤§æ–¹ã€‘/dafang/ generousï¼Œã€éš¨ä¾¿ã€‘/fangbian/ comfortableï¼Œã€èˆ’æœã€‘/shufu/ comfortable, etc. and a sentence pattern using "Adjective+Adjective's form +ã€ä¸€é»žã€‘, such ã€å°å°ã€‘/xiao xiao/ "small". The category of the second group of "comparative + adjective +ã€ä¸€é»žã€‘'a little' " has 65 (8.6%) sentences. There are 42 (5.58%) sentences in the third group of "Adjective + ã€äº†ã€‘/le/ + a little " category. The fourth group of "ã€å¤ªã€‘/tai/+ Adjective + a little bit" structure has only 14 sentences (1.87%). Keywords: adjective, a little, Mandarin Chinese, Indonesian language, comparison